Rich-Club Analysis of Structural Brain Network Alterations in HIV Positive Patients With Fully Suppressed Plasma Viral Loads - Aili, Xire; Wang, Wei; Zhang, Aidong; Jiao, Zengxin; Li, Xing; Rao, Bo; Li, Ruili; Li, Hongjun (Frontiers in Neurology, 2022)
Objective Even with successful combination antiretroviral therapy, human immunodeficiency virus positive (HIV+) patients continue to present structural alterations and neuropsychological impairments. The purpose of this study is to investigate structural brain connectivity alterations and identify the hub regions in HIV+ patients with fully suppressed plasma viral loads. Methods In this study, we compared the brain structural connectivity in 48 HIV+ patients treated with combination antiretroviral therapy and 48 healthy controls, using diffusion tensor imaging. Further comparisons were made in 24 patients with asymptomatic neurocognitive impairment (ANI) and 24 individuals with non-HIV-associated neurocognitive disorders individuals, forming a subset of HIV+ patients. The graph theory model was used to establish the topological metrics. Rich club analysis was used to identify hub nodes across groups and abnormal rich club connections. Correlations of connectivity metrics with cognitive performance and clinical variables were investigated as well. Results At the regional level, HIV+ patients demonstrated a decreased degree centrality (DC), betweenness centrality (BC), and nodal efficiency (NE) at the occipital lobe and the limbic cortex; increased BC and nodal cluster coefficient (NCC) in the occipital lobe, frontal lobe, insula, and thalamus. The ANI group demonstrated a significant reduction in the DC, NCC, and NE in widespread brain regions encompassing the occipital lobe, frontal lobe, temporal pole, and limbic system. These results did not survive from the Bonferroni correction. HIV+ patients and ANI group had similar hub nodes, that were mainly located in the occipital lobe and subcortical regions. The abnormal connections were mainly located in the occipital lobe in the HIV+ group, and in the parietal lobe in the ANI group. The BC in the calcarine fissure was positively correlated with complex motor skills. Disease course was negatively correlated with NE in the middle occipital gyrus. Conclusion: The results suggest that the occipital lobe and the subcortical regions may be important in structural connectivity alterations and cognitive impairment. Rich club analysis may contribute to our understanding of the neuropathology of HIV-associated neurocognitive disorders.